Digital pathways for enriched communities and futures: Plantation heritage in São Tomé and Príncipe - Stellacci, S.; Eloy, S. (Digital approaches to inclusion and participation in cultural heritage: Insights from research and practice in Europe, 2023)
In revolutionizing the type and the speed of information available, digital globalization has reshaped perspectives and cross-border actions in various domains worldwide. However, these knowledge-intensive flows have scarcely influenced practice around heritage in least developed countries (LDCs). Historical biases, exacerbated by systemic inequities and ethnic divisions, still represent some of the most relevant barriers to 21st-century development, inhibiting the appropriate valuation of shared cultural heritage. This study seeks to shed light on the roças, a widespread system of cocoa and coffee plantations established in São Tomé and Príncipe by Portuguese colonizers of the mid-19th. We show how roças and other shared heritage sites represent living sources for intergenerational learning. E-learning tools can be an important driver of systemic cultural overhaul, sustainable heritage management, global peacebuilding, and social cohesion, provided that broad communities, including descendants from former colonized countries, are actively involved throughout the critical design process of reinterpreting those sites.